Lung‐Targeted Rnai Therapeutics: Lung‐Endothelium‐Targeted Nanoparticles Based on a pH‐Sensitive Lipid and the GALA Peptide Enable Robust Gene Silencing and the Regression of Metastatic Lung Cancer (Adv. Funct. Mater. 18/2019). (2nd May 2019) - Abd Elwakil, Mahmoud M.; Khalil, Ikramy A.; Elewa, Yaser H. A.; Kusumoto, Kenji; Sato, Yusuke; Shobaki, Nour; Kon, Yasuhiro; Harashima, Hideyoshi
Abstract : Engineering nanocarrier systems for efficient small interfering RNA (siRNA) delivery requires advanced materials that can achieve specific cellular targeting together with efficient intracellular trafficking for reaching target sites in the cytosol. In article number1807677, Ikramy A. Khalil, Hideyoshi Harashima, and co‐workers use nanoparticles modified with the GALA peptide as targeted therapy for the lung endothelium, resulting in a robust gene knockdown. The nanoparticles are successfully applied for the regression of metastatic lung cancer.